2023
DOI: 10.3390/en16145303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Regenerative Braking on Battery Life

Abstract: It is a well-known fact that automotive industries in every country are shifting towards electric vehicles (EVs) and in the days to come it is expected that the industry will become dominated by them, along with hybrid electric vehicles (HEVs). Unfortunately, the acceptance of EVs for mobility is affected by its poor range per charge. Thus, energy optimization and waste energy recuperation are currently in need. A promising method to recover energy that is lost during vehicle deceleration is regenerative braki… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…Scientific studies conducted for this purpose have shown that regenerative braking can increase the range of EVs by 20-30% [11][12][13]. However, electrical conditions such as fast charging and frequent charging, which we can see as the reason for this situation, cause negative effects on the vehicle battery and cause the battery pack or battery cells to deteriorate [14][15][16][17]. In addition to increasing the range of EVs, preventing battery aging is critical for ensuring economic and environmental sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific studies conducted for this purpose have shown that regenerative braking can increase the range of EVs by 20-30% [11][12][13]. However, electrical conditions such as fast charging and frequent charging, which we can see as the reason for this situation, cause negative effects on the vehicle battery and cause the battery pack or battery cells to deteriorate [14][15][16][17]. In addition to increasing the range of EVs, preventing battery aging is critical for ensuring economic and environmental sustainability.…”
Section: Introductionmentioning
confidence: 99%